2003
DOI: 10.1194/jlr.m300031-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A decreased expression of angiopoietin-like 3 is protective against atherosclerosis in apoE-deficient mice

Abstract: KK/Snk mice (previously KK/San) possessing a recessive mutation ( hypl ) of the angiopoietin-like 3 ( Angptl3 ) gene homozygously exhibit a marked reduction of VLDL due to the decreased Angptl3 expression. Recently, we proposed that Angptl3 is a new class of lipid metabolism modulator regulating VLDL triglyceride (TG) levels through the inhibition of lipoprotein lipase (LPL) activity. In this study, to elucidate the role of Angptl3 in atherogenesis, we investigated the effects of hypl mutation against hyperlip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 43 publications
(44 reference statements)
7
62
0
1
Order By: Relevance
“…Inactivation of ANGPTL3 lowered plasma cholesterol levels in Apoe ÏȘ / ÏȘ mice ( Fig. 2A ), as was reported previously ( 22,23 ). Similar reductions were observed in Apoe…”
Section: Both Immunological and Genetic Inactivation Of Angptl3 Reducsupporting
confidence: 90%
See 2 more Smart Citations
“…Inactivation of ANGPTL3 lowered plasma cholesterol levels in Apoe ÏȘ / ÏȘ mice ( Fig. 2A ), as was reported previously ( 22,23 ). Similar reductions were observed in Apoe…”
Section: Both Immunological and Genetic Inactivation Of Angptl3 Reducsupporting
confidence: 90%
“…The nature of the pathway by which ANGPTL3 inactivation promotes the clearance of ApoB is not known. ANG-PTL3 defi ciency is associated with lower cholesterol levels in mice lacking either ApoE or LDLR ( 22,23 ), and the present study extends these fi ndings to LRP1 and syndecan 1. Thus, the increased clearance of ApoB-containing lipoproteins presumably involves a noncanonical pathway that does not require ApoE, the LDLR, LRP1, or syndecan 1.…”
Section: Inactivation Of Angptl3 Does Not Affect Fatty Acid Uptake Bysupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, Minicocci et al ( 11 ) reported lower fasting glucose and the lack of diabetes mellitus among homozygous carriers of inactivating mutation in the ANGPTL3, but the consistency of these fi ndings remain to be confi rmed. Finally, it has been suggested that the defi ciency of ANGPTL3 may be protective against atherosclerosis ( 22 ). In a previous report, homozygous FHBL2 subjects did not show evidence of history of cardiovascular disease, but the low number of cases investigated precluded any defi nitive conclusion ( 11 ).…”
mentioning
confidence: 96%
“…However, the concentrations of ANGPTL3 used in these studies were supraphysiological. Moreover in some (14,17), although not all (8) studies, the increase in LPL activity in Angptl3 −/− mice has been modest. ANGPTL3 also inhibits the activity of endothelial lipase (18,19), which catalyzes the hydrolysis of phospholipids in circulating lipoproteins.…”
mentioning
confidence: 99%